ANALISIS MISKONSEPSI MATERI LARUTAN PENYANGGA DALAM PEMBELAJARAN BERBASIS MASALAH BERBANTUAN MEDIA INTERAKTIF (Universitas Negeri Semarang, 2019)
This study aimed to analyze the misconceptions of the students through a posttest after interactive learning with a model of Problem Based Learning. The study was conducted in SMA N 1 Batang with sampling research done by purposive sampling was XI MIA-G in even semester with the subject matter of the Buffer Solution. The research designed by descriptive analysis with data collection through the documentation, written tests, questionnaires, and interviews. The result of overall analysis concept gained 300 kinds of the students from the posttest result. The result of concept patterns in XI MIA-G showed that most of the students understand the concept was 83%, a small percentage of the students which experienced misconceptions was 15,33% and which didn’t understand the concept was 1,67%.